2021
DOI: 10.3390/ani11051370
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Intelectin 2 Expression as a Biomarker of Paratuberculosis Disease Progression

Abstract: Paratuberculosis (PTB), a chronic granulomatous enteritis caused by Mycobacterium avium subsp. paratuberculosis (MAP), is responsible for important economic losses in the dairy industry. Our previous RNA-sequencing (RNA-Seq) analysis showed that bovine intelectin 2 (ITLN2) precursor gene was overexpressed in ileocecal valve (ICV) samples of animals with focal (log2 fold-change = 10.6) and diffuse (log2 fold-change = 6.8) PTB-associated lesions compared to animals without lesions. This study analyzes the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Likewise, the individual mean expression levels of ABCA13 in the focal, multifocal and diffuse groups was significantly higher than in the control group (see Figure 1, Table 2). This expression pattern across pathological forms was similar to that observed for intelectin 2 (ITLN2) in the ileocecal valve (ICV) in a recently published study (81). These findings validated our initial study where RNA-seq results showed that the ABCA13 and ITLN2 genes were overexpressed in peripheral blood (log2 fold change = 3.7) and ICV (log2 fold change 10.6) of animals with focal lesions compared to control animals without lesions (35).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, the individual mean expression levels of ABCA13 in the focal, multifocal and diffuse groups was significantly higher than in the control group (see Figure 1, Table 2). This expression pattern across pathological forms was similar to that observed for intelectin 2 (ITLN2) in the ileocecal valve (ICV) in a recently published study (81). These findings validated our initial study where RNA-seq results showed that the ABCA13 and ITLN2 genes were overexpressed in peripheral blood (log2 fold change = 3.7) and ICV (log2 fold change 10.6) of animals with focal lesions compared to control animals without lesions (35).…”
Section: Discussionsupporting
confidence: 89%
“…A total of 704 Holstein-Friesian cows, with an average age of 5.2 years ranging from 0.5 to 13.4, were included in this study. The positive reference group consisted of 566 cows from 8 different regions of Spain (Basque Country, Catalonia, Navarra, Aragón, Cantabria, Castilla y León, La Rioja and Asturias) commercially slaughtered in five abattoirs located in the Basque Country and Asturias ( 23 , 36 , 81 ). The negative reference group consisted of 138 live cows from 4 PTB-free farms of Asturias.…”
Section: Methodsmentioning
confidence: 99%
“…Animals are infected early in life through the fecal-oral route but clinical onset appears when animals are 18 months or older. Current diagnostic tests, ELISA and fecal PCR, often fail to detect MAP-infected cattle early in the course of infection ( 3 , 4 ). According to their extension, cellular infiltrate, and amount of MAP, PTB-associated histological lesions have been classified into the following categories: focal, multifocal, and diffuse (diffuse paucibacillary, diffuse intermediate, and diffuse multibacillary) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using RNA-Seq technology we previously identi ed a biomarker of PTB progression, the precursor of the bovine intelectin 2 (ITLN2), which was overexpressed in ICV samples of animals with focal (log 2 fold-change = 10.6) and diffuse (log 2 foldchange = 6.8) lesions compared with animals without visible lesions [31]. More recently, we have demonstrated that the quanti cation of bovine ITLN2 secreting cells by immunohistochemical analysis of ICV sections could constitute a good post-mortem tool, complementary to histopathology, to improve the detection of focal lesions which may sometimes be di cult to detect [32]. In an attempt to test whether the focal lesions were controlled by a speci c genetic, a GWAS comparing animals with focal vs multifocal and focal vs diffuse lesions was performed (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Using RNA-Seq, we previously detected that the cholesterol route (bta04977) was dysregulated in the ICV of cows with diffuse lesions versus the control group with four upregulated genes matching this route (APOA1, APOC3, APOA4, APOB) [31]. In addition, the top upregulated gene in peripheral blood of animals with focal lesions versus control cows was the cassette subfamily A member 13 (ABCA13), a gene that accelerates cholesterol internalization and accumulation in intracellular vesicles [31][32]41]. In agreement with our data, recent evidence suggests that MAP-infected macrophages accumulate intracellular cholesterol droplets and depict a foam cell phenotype providing an enriched environment for MAP survival [42][43].…”
Section: Discussionmentioning
confidence: 99%